The Humanities and Arts in The Gerontological Society of America. (15th May 2020) - Achenbaum, W Andrew
Abstract: Perspectives from the humanities and arts (H&A) on old age have deep roots in history; they emerged over the centuries along with concurrent scientific investigations. Provisionally invited into the scientific ranks of The Gerontological Society of America (GSA) during the late 1970s, H&A prospered, but grew amid tensions. During 75th-anniversary celebrations, Society members will assess H&A's role in GSA. How can H&A continue to enrich scientific research? How can H&A further advance its own meaningful contributions? Or, should H&A and GSA reconfigure its partnership?